Antibacterial Activity of Three Algal Genera against some Pathogenic Bacteria - Janan Jabbar Toma; Farhad Hassan Aziz (مجلة بغداد للعلوم)
In the current study, three types of algae namely Tetradesmus nygaardi (MZ801740), Scenedesmus quadricauda (MZ801741) and Coelastrella sp (MZ801742) were extracted by 95% ethanol and hexane against two types of gram positive and two types of gram negative bacteria by wells diffusion methods. Eleven concentrations from the extract of algae (2, 5, 10, 15, 20, 25, 30, 35, 40, 45 and 50 mg/ml) were utilized. It was noticed that ethanolic extraction was more effective than hexane in Scenedesmus quadricauda than the two other mentioned algal species against all pathogenic bacteria, Acintobacter baumanii (ATCC: 19606), Klebsiella pneumonia (ATCC: 13883) Enterococcus faecalis (ATCC: 29212) and Staphylococcus aureus (ATCC: 14028). In addition to that, extraction of Tetradesmus nygaardi by hexane was more effective than ethanol against all studied pathogenic bacteria. Extract of Coelastrella sp by Ethanol showed weak effect against all pathogenic bacteria compared with the other types of algae. Many chemical compounds which possess antibacterial activities were obtained through analyzing the extraction of algae by gas chromatography–mass spectrometry (GC-MS)